Analysis of User Experience on The Bc Hni 1 E-Commerce Website Using The Ueq Method - Setianingsih, Ani; Verry, V; Zein, Mochamad T.A Aziz (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2025)
This research was conducted at the HNI (Halal Network International) Cilacap 1 Business Center with a focus on analyzing the user experience of E-Commerce sites using the User Experience Questionnaire (UEQ) method. The background of this research is the progress of the industrial era 4.0 and the increasing use of the internet in Indonesia which changes consumer behavior. The goal is to evaluate aspects of user experience, including attractiveness, clarity, efficiency, accuracy, stimulation, and novelty on the BC HNI 1 E- Commerce website. This research uses a quantitative approach with a population of users or consumers who access the website. Data were collected through observations, interviews, questionnaire surveys, and literature studies. The research instrument is a UEQ questionnaire consisting of 26 items divided into 7 scales. Data analysis includes demographic analysis, validity test using Pearson Product Moment, and reliability test using Cronbach's Alpha. The results showed that the majority of respondents were women (72%) and young individuals under 30 years old (64%). All statements were declared valid and the research instrument was declared reliable with a Cronbach's Alpha value of 0.777. The user experience evaluation showed that all measured aspects, including attractiveness (mean 1.443), clarity (mean 1.830), efficiency (mean 1.710), accuracy (mean 1.815), stimulation (mean 1.595), and novelty (mean 1.560) received positive evaluation scores. The benchmark results show that attractiveness scored above average, clarity and efficiency scored good, and accuracy, stimulation, and novelty scored excellent.